청소년 비행 정도와 부모 - 자녀간 의사소통 가족의 응집 및 적응과의 관계 - 민하영(Ha Yeoung Min) (Korean Journal of child studies, 1992)
The purpose of this study was to identify the relation between juvenile deliquency and parent-adolescent communication, the family cohesion and adaptability as variables of psychological environment of the family. The subjects were 143 juvenile deliquents in jail, aged 16 to 19, and 347 9th, 10th, 11th, 12th grade students who resided in low income areas in Seoul and Taegu. The research data were collected by structured questionnaire. 143 juvenile delinquents and 87 students whose degree of deliquency was more than M+(0.5*S.D) were selected as the final data source. The statistical methods were frequency percentile, pearson's correlation, one-way ANOVA. Scheffe'test and multiple regression analysis. The major findings showed that (1) juvenile deliquency was significantly related to father-closed communication type. (2) juvenile deliquency was significantly related to low family cohesion and adaptability, (3) the family cohesion and adaptability was positively correlated with parent-adolescent communication. Father-adolescent communication had more important effect upon the family cohesion and adaptability than mother-adolescent communication.